Quadruple and Quintuple Helix Innovation: A Multi-Actor Approach in Reducing the Prevalence of Stunting at Jeneponto Regency, Indonesia - Mustari, Nuryanti; Wahid, Nur; ., Muhajir; ., Herman; Arfah, Iqbal Nur; Chandra, Diky (South Eastern European Journal of Public Health, 2024)
This study aims to determine collaboration between government actors, industry, universities, non-governmental organizations and the media in reducing the prevalence of stunting at Jeneponto Regency. Qualitative methods used by collecting data through interviews, documentation and observation. The results of the data obtained then transcribed into an accurate tool called Nvivo 12 plus. The analysis units used main map and work frequency. This study found that collaboration between government, private, university, non-governmental organizations and media actors had a significant influence in reducing the prevalence of stunting at Jeneponto Regency. To overcome the high stunting rate in Jeneponto Regency, collaboration between actors was needed, including government actors, industry, educational institutions, non-governmental organizations and media. All these actors must work well together. Apart from that, it was also important to know the causes of stunting rate to remain high in Jeneponto Regency. The cause of stunting was the environment, including sanitation and access to clean water, which was very important to prevent stunting.